Análise de desempenho de fluídos de base vegetal aplicados por MQL no acabamento gerado pelo fresamento frontal do aço inoxidável ASTM 743 CA6NM - Borges, Julian Conterno (2019)
The present work evaluated the application of refined vegetable oils such as cotton, canola, sunflower, corn and soybean as cutting fluid, applied in the form of MQL as well as Quimaticjet fluid, and also with the use of Bondmann B90 fluid applied by the system abundance in machinability of ASTM 743 CA6NM martensitic stainless steel through the front milling process to investigate the influence of cutting parameters on the surface roughness of machined parts. Several experiments were designed and analyzed with the aid of factorial design, and the results indicated that the cutting speed has no significant influence and that the advance has a significant influence on the measured roughness parameters Ra and Rz. To choose the fluid that best behaved in the experiments, we used the t-test, which statistically excluded fluid B90, leaving other conditions very close to the values of Ra and Rz. It was also compared, through the value of the average values of the roughness Ra, the performance obtained by the fluids to evaluate the differences between them in relation to a machining condition.